2000
DOI: 10.1161/01.str.31.7.1656
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Variations in Circle of Willis in Atherosclerotic Population Assessed by Means of Transcranial Color-Coded Duplex Ultrasonography

Abstract: Background and Purpose-Transcranial color-coded duplex ultrasonography combined with common carotid artery (CCA) compression can be used to assess the collateral function of the circle of Willis. The aim of this study was to assess the unknown fraction of hemodynamic functional anterior and posterior communicating arteries (AcoA and PcoA, respectively) in an atherosclerotic population with no cerebrovascular symptoms. Methods-In 76 patients with a mean age of 61 (35 to 89) years, the blood flow velocity change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 30 publications
7
46
0
1
Order By: Relevance
“…Bilateral lack of PComAs was the most frequent posterior variant published in the literature [6,[12][13][14], although its prevalence varied. This variant was reported in about 30.00% of the subjects undergoing CTA examinations, which was twice as often as in the aforementioned MRA and TCCD studies [6,9]. The incidence of FTP has been reported as ranging from 11.20% to 18.00% in different studies [6,14], whereas in the present study it was found to occur in 16.40% of the cases.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Bilateral lack of PComAs was the most frequent posterior variant published in the literature [6,[12][13][14], although its prevalence varied. This variant was reported in about 30.00% of the subjects undergoing CTA examinations, which was twice as often as in the aforementioned MRA and TCCD studies [6,9]. The incidence of FTP has been reported as ranging from 11.20% to 18.00% in different studies [6,14], whereas in the present study it was found to occur in 16.40% of the cases.…”
Section: Discussionsupporting
confidence: 43%
“…Conclusions based on the comparison of data acquired using different methods seem to be questionable. This is due to the fact that each particular evaluation technique has different characteristics and limitations [5,6,9]. Furthermore, it should be noted that a number of previously published studies were carried out on patients with cerebrovascular disorders [3,6,8,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 TCCD has been reported to be a valuable method to detect stenoses of less than 50% in large intracranial vessels, with a high accuracy, 22 and to assess the collateral function of smaller communicating vessels. 23,24 Furthermore, TCCD enables the sonographer to correct the angle of insonation, which could be larger than expected in elderly patients with tortuous vessels, in patients with intracranial stenosis, and when a mass effect is present. 25 Thus, TCCD may play a role in complicated MCA lesions.…”
Section: Discussionmentioning
confidence: 99%